Evaluation of Findings and Neonatal Outcome in Fetal Growth Restriction: A Comparative Study - Rajender Kumar (Asian Journal of Medical Radiological Research, 2020)
Background: Fetal growth restriction (FGR) is a condition in which a foetus fails to reach its genetically determined growth potential. It affects 5-10% of pregnancies. Subjects and Methods: A total of 74 women with singleton pregnancies of 28 weeks or more were examined using Doppler examinations based on inclusion and exclusion criteria. Results: Out of the 74 neonates, 67 (90.5%) had a birth weight of 1.5-2.5 kg, 05 (6.8%) weighed more than 2.5 kg, and 2 (2.7%) weighed less than 1.5 kg. Fifty-seven newborns needed to be admitted to the NICU, with  27 (47.4%) born as term neonates and 30 (52.6%) born as pre-term neonates. In the NICU, 2 (3.6%) neonates needed ventilator assistance, 11 (20.0%) neonates needed CPAP, and the rest needed oxygen support. Sepsis was treated in 4 (5.4%) of the newborns. Conclusion: The newborn suffers significant perinatal and long-term consequences as a result of foetal growth restriction.